Akibat Hukum Penebangan Hutan secara Liar - Putu Ayu Irma Wirmayanti; Ida Ayu Putu Widiati; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2021)
Formerly the Indonesia forest rich in diversity and different kinds of populations in them but this time the forests of Indonesia into the world's endangered forests because of the result of the destruction of forests by cutting down trees in the wild. Wild forest logging becomes one of the factors of damage in forest area is currently logging the forest resulting in negative impact be bald. Although there are already rules governing logging prohibitions are still many wild is also the person who is doing the logging of trees in the forest are wild. The problem of this research is to 1) How is regulate about the prohibition on logging in wild? 2) How is the application of the sanctions for the perpetrators of the deforestation in the wild? Research methods used are normative, legal research methods with the study of the library of primary and secondary legal materials. Research results can be concluded that: 1) the prohibitions of wild forest logging is regulated in the law of forestry Number 41 Year 1999, Act No. 18 years 2013 on prevention and eradication of Forest Destruction and regulations Government forest protection Number 28-year 1985. 2) Penalties for perpetrators who commit illegal logging may include civil penalties, administrative sanctions and criminal sanctions. Of that society expected to care about the environment, because one of the causes of the occurrence of natural disasters, namely wild deforestation.